New understanding on regulating the crystallization and morphology of the beta-polymorph of isotactic polypropylene based on carboxylate-alumoxane nucleating agents - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Macromolecules, 2016)
Carboxylate alumoxane derived from p-n-alkylbenzoic acids, where n-alkyl group changes from 2 to 8 carbon atoms, exhibits dual nucleating ability and nucleates isotactic polypropylene (iPP) into predominantly in the beta-phase under specific conditions. The selectivity of the beta-phase nucleation depends on the concentration of the nucleating agent, end melting temperature and cooling rate. The beta-phase obtained from p-n-alkylbenzoate-alumoxanes is compared with the beta-phase obtained from calcium pimelate (CaP), an efficient beta-phase selective, nucleating agent, using the results from DSC, WAXS, and SAXS analysis. The lamellar morphology of iPP nucleated with different nucleating agents crystallized at different crystallization temperatures (T-C) under controlled nonisothermal conditions are evaluated using SAXS analysis. The long period increases with increasing crystallization temperature and the long period of the beta-phase is always larger than that of the alpha-phase for a given crystallization temperature. Furthermore, the variation of long period with crystallization temperature clearly brings out two crystallization temperature ranges; the low temperature range and the high temperature range. However, the beta-phase shows a lower changeover temperature compared to that of the alpha-phase. The one-dimensional correlation analysis of the beta-phase shows that the thickness of the crystal lamellae (lc) increases with T-C and exhibits the low and high crystallization temperature ranges, while the thickness, of the amorphous layer (la) more or less remains constant. In-situ high temperature WAXS studies capture the beta-phase to the a-phase transition and the transformed material con-elates well with the lamellar thickness of the beta-phase. The morphological difference between the alpha- and the beta-phases are discussed and attributed to the differences in the impact properties and the melting temperature. This study clearly demonstrates that the lamellar morphology mainly depends on the T-C and not on the nature of the nucleating agents.